Enhancement of protein flocculant properties through carboxyl group methylation and the relationship with protein structural changes. Issue 14 (30th November 2021) - Garcia, Rafael A.; Qi, Phoebe X.; Essandoh, Matthew; Bumanlag, Lorelie P.
Abstract: Some proteins will function as flocculants to clear water of suspended particles. Prior work has shown that covalent methylation of a protein's carboxyl groups can enhance that protein's flocculant activity; this effect is usually attributed to the reduction in negative charges on the protein. We present results generated using four proteins which show that much of the flocculant activity enhancement occurs in a very short time at the beginning of the methylation reaction, before most of the carboxyl groups have been methylated. A variety of techniques are used to show that the methylation reaction has unintended effects on protein structure and aggregation, and that these effects may play an important role in enhancing protein flocculant activity. The observed enhancement in flocculant activity results from both charge and structural modification. Graphical Abstract: Abstract : UF0001